Devaluation (levels versus rates) and balance of payments in a cash-in-advance economy - Alberto Petrucci (Fondazione Eni Enrico Mattei (FEEM), 2002)
This paper investigates the consequences of the currency devaluation, both in levels and rates, on the balance of payments in a cash-in-advance economy with finite horizons, endogenous capital accumulation and international capital immobility. In this context, a once and for all currency devaluation induces a balance of payments surplus, whereas a sustained increase in the rate of devaluation produces, in principle, an ambiguous effect on the balance of payments. If however non-restrictive assumptions on some structural parameters are made, an increase in the devaluation rate leads to a balance of payments surplus, the exact opposite of Calvo's result (1981).
Keywords: E21; E62; 330; Devaluation; balance of payments; cash-in-advance constraint; overlapping generations; Abwertung; Zahlungsbilanz; Cash-in-Advance-Restriktion; Kleine offene Volkswirtschaft; Theorie